Biosafety research for non-target organism risk assessment of RNAi-based GE plants - Roberts, Andrew F.; Devos, Yann; Lemgo, Godwin N. Y.; Zhou, Xuguo (Frontiers in Plant Science, 2015)
RNA interference, or RNAi, refers to a set of biological processes that make use of conserved cellular machinery to silence genes. Although there are several variations in the source and mechanism, they are all triggered by double stranded RNA (dsRNA) which is processed by a protein complex into small, single stranded RNA, referred to as small interfering RNAs (siRNA) with complementarity to sequences in genes targeted for silencing. The use of the RNAi mechanism to develop new traits in plants has fueled a discussion about the environmental safety of the technology for these applications, and this was the subject of a symposium session at the 13th ISBGMO in Cape Town, South Africa. This paper continues that discussion by proposing research areas that may be beneficial for future environmental risk assessments of RNAi plants, with a particular focus on non-target organism assessment.